Enhancing Motor Skill Learning with Transcranial Direct Current Stimulation – A Concise Review with Applications to Stroke - Madhavan, Sangeetha; Shah, Bhakti (Frontiers in Psychiatry, 2012)
In the past few years, there has been a rapid increase in the application of non-invasive brain stimulation to study brain-behavior relations in an effort to potentially increase the effectiveness of neuro-rehabilitation. Transcranial direct current stimulation (tDCS), an emerging technique of non-invasive brain stimulation, has shown to produce beneficial neural effects in consequence with improvements in motor behavior. tDCS has gained popularity as it is economical, simple to use, portable and increases corticospinal excitability without producing any serious side effects. As tDCS has been increasingly investigated as an effective tool for various disorders, numerous improvements and developments have been proposed with respect to this technique. tDCS has been widely used to identify the functional relevance of particular brain regions in motor skill learning and also to facilitate activity in specific cortical areas involved in motor learning, in turn improving motor function. Understanding the interaction between tDCS and motor learning can lead to important implications for developing various rehabilitation approaches. This paper provides a brief overview of tDCS as a neuromodulatory technique and a comprehensive understanding of the interaction of tDCS with motor learning. The paper further briefly goes through the application of this priming technique in the stroke population.